A Systematic Literature Review of Performance Hospital Supply Chain Management - Louah, Soulaiman; Sarir, Hicham; Kriouich, Mohamed (Journal of Robotics and Control (JRC), 2024)
Over the last few decades, globalization has driven up the demand for hospital Supply Chain Management (SCM) with the goal of bio-medical development and improving performance. This review aims to offer both a qualitative and quantitative comprehension of the hospital SCM re-search field's overall developmental trend. By using the methodology science mapping approach are visualize the organization of academic knowledge, 87 significant papers, that were published between 2002 and 2023 in total due to their importance in recent years, were located, expanded upon, and summarized. Bibliographic analysis for under-standing the global research state and academic develop-ment was performed on visualized statistics can help identi-fy trends in data about co-occurring keywords, interna-tional cooperation, journal allocation/co-citation, and view clusters of study subjects based on this five categorization, 22 sub-branches in total of hospital SCM identification and topical discussion of knowledge were conducted, namely (i) technologies; (ii) planning; (iii) supply chain field in hospi-tals; (iv) logistics and (v) environmental. Lastly, suggestions for future study directions and current knowledge gaps were made due to constraints of international cooperation and insufficient platforms to quickly advance innovation technology research. The results contribute to a methodical intellectual representation of the current state of hospital SCM research. Furthermore, it offers heuristic ideas to practitioners and researchers to control the quality of de-veloped healthcare and logistics services.